Job insecurity, leadership empowerment behaviour, employee engagement and intention to leave in a petrochemical laboratory - Sonet van Schalkwyk (SA Journal of Human Resource Management, 2010)
Orientation: Engaging individuals at work plays an important role in retaining them. Job security and leadership empowerment behaviour are antecedents of employee engagement. Research purpose: The objective of this study was to investigate the relationship between job insecurity, leadership empowerment behaviour (as perceived by the employees who report to leaders), employee engagement and intention to leave their jobs in a petrochemical laboratory.